Analisis Gagasan Kang Dedi Mulyadi tentang Pendidikan Karakter Remaja melalui Model Barak Militer - Parhi, Nurmu’izzatin Zaharatul (Muadalah, 2025)
The ongoing character crisis among Indonesian youth signifies the fragile ethical and social foundation of the younger generation. In this context, character education is no longer a supplementary initiative but an urgent necessity requiring a new approach that is not only normative but also practical and transformative. One innovative effort to address this challenge is the character education program through Military Barracks initiated by Kang Dedi Mulyadi, Governor of West Java for the 2025–2030 term. This study aims to explore the conceptual framework of character education within the program and analyze it through Lawrence Kohlberg's theory of moral development. The research employs a qualitative literature study method. Data were collected from various academic sources, including books, scholarly articles, policy documents, and relevant media reports, and were analyzed using a descriptive-analytical approach. The findings reveal that the military barracks program is not built upon a repressive approach but functions as a moral laboratory that integrates military discipline, humanistic values, and intensive value formation. Participants undergo behavioral transformation through physical routines, spiritual reflection, open dialogue, and empathetic interaction with trainers and facilitators. Within Kohlberg's theoretical framework, this process shifts the participants' morality from the pre-conventional stage—driven by punishment avoidance—to the conventional and post-conventional stages, where values are embraced due to internal moral awareness rather than external pressure. This study contributes academically by highlighting the reinforcement of a contextual and humanistic approach to character education. The military barracks are shown to be a new space for value formation that not only promotes discipline but also revives integrity, empathy, and social responsibility among adolescents. This model opens up new horizons for character education policies that are more adaptive to ethical challenges in the contemporary era.